β-arrestin-2 is an essential regulator of pancreatic β-cell function under physiological and pathophysiological conditions - Lu Zhu (Nature Portfolio, 2017)
Beta-arrestins have key roles in development and metabolic functions as euglycaemic control and insulin sentitivity. Here Zhuet al. show that beta-arrestin-2 regulates insulin secretion and glucose tolerance in mice by promoting CAMKII functions in beta cells.